EFISIENSI PEMASARAN BAWANG MERAH DI DESA TONSEWER KECAMATAN TOMPASO BARAT KABUPATEN MINAHASA - Erwin . Ali; Celcius . Talumingan; Paulus A. Pangemanan; Ribka M. Kumaat (Sam Ratulangi University, 2015)
The research result showed that there was 2 marketing channel of onion in Tonsewer village, Tompaso Barat Sub District, Minahasa Regency that are: (1) Channel 1 : Farmer→ Retailer→ Consumer, (2) Channel 2 : Farmer→ Collecting trader→ Retailer→ Consumer. The highest marketing margin was obtained by collecting trader that is Rp. 4.333,33 (Karombasan market), did the lowest is Rp. 2.333,33 (Tomohon market). While the highest marketing margin obtained by retailer that is Rp. 4.000,00 (Karombasan market) and the lowest is Rp. 2.333,33 (Langowan and Kawangkoan market). The highest profit margin is Rp. 3.924,48 (Karombasan market) and the lowest is Rp. 2.246,16 (Langowan and Kawangkoan market). Keywords : marketing efficiency, marketing margin, profit margin.